Estrabismo y ambliopía en ojo izquierdo en paciente masculino de 6 años. - Miranda Valenzuela, Mayerly Lizbeth (2022)
One of the common alterations that can be detected in children is strabismus, which consists of an ocular deviation that causes problems in visual acuity and hinders binocular vision. It also makes it difficult to see in 3d, and decreases the depth of the visual field. There are several causes that can generate strabismus, it can be caused by nerve injuries, a malfunction of the muscular system that surrounds the eye. The present case study deals with a 6-year-old patient who presents amblyopia in the left eye due to accommodative strabismus. This has generated a series of discomforts such as headaches, difficulty focusing, discomfort in performing her tasks. Correct treatment must be identified and prescribed in order to preserve the patient's visual quality. Amblyopia can affect visual acuity and treatment is necessary to prevent vision loss. One of the alternatives is the use of atropine drops, which are placed in the healthy eye so that the weak eye is forced to work, this stimulates the brain to develop better vision. Another visual therapy that is implemented is the use of the occlusion patch. Once the respective examinations have been carried out, the use of prescription lenses as an optical aid and the implementation of visual therapies using the occlusion method are determined in order to encourage the amblyopic eye to perform its function adequately.